Efficacy and safety of brodalumab in patients with psoriasis who had inadequate responses to ustekinumab: subgroup analysis of two randomized phase III trials. (27th December 2018) - Langley, R.G.; Armstrong, A.W.; Lebwohl, M.G.; Blauvelt, A.; Hsu, S.; Tyring, S.; Rastogi, S.; Pillai, R.; Israel, R.
Summary: Background: Brodalumab, a fully human anti‐interleukin‐17 receptor A monoclonal antibody, has demonstrated superior efficacy and safety over ustekinumab as induction therapy for moderate‐to‐severe psoriasis. Objectives: To evaluate the efficacy and safety of brodalumab through week 52 in patients who had inadequate responses to ustekinumab. Methods: A subgroup analysis of the phase III AMAGINE‐2/‐3 double‐blind randomized controlled trials was performed. Participants were aged 18–75 years and had a Psoriasis Area and Severity Index (PASI) ≥ 12, static Physician's Global Assessment score ≥ 3 and involvement of ≥ 10% body surface area. The studies were registered at ClinicalTrials.gov: AMAGINE‐2, NCT01708603; AMAGINE‐3, NCT01708629. Results: At baseline, patients with or without prior biologic experience who had an adequate response at week 16 on ustekinumab or brodalumab had lower rates of involved body surface area, PASI, prior biologic use, psoriatic arthritis and body mass index than patients who experienced inadequate response at or after week 16. Among patients who experienced inadequate response to ustekinumab, those rescued with brodalumab had PASI ≥ 75%, ≥ 90% and 100% improvement response rates of 72·6%, 58·1% and 36·3%, respectively, at week 52 compared with 61·7%, 25·5% and 5·4%, respectively, in patients who continued ustekinumab. Exposure‐adjusted rates of treatment‐emergent adverse events were similar among patients rescued with brodalumab (377·3 adverse events per 100 patient‐years) and those who remained on ustekinumab (389·9 adverse events per 100 patient‐years). Conclusions: Among patients who experienced inadequate responses to ustekinumab, rescue with brodalumab improved skin clearance outcomes compared with continuing ustekinumab. Abstract : What's already known about this topic? Among biologics used to treat psoriasis, brodalumab provides a unique mechanism of action by antagonizing interleukin‐17 receptor A. In the AMAGINE‐2/‐3 randomized controlled trials, brodalumab demonstrated superior skin clearance efficacy and safety compared with ustekinumab as induction therapy in patients with psoriasis. Brodalumab is approved for the treatment of moderate‐to‐severe psoriasis in adults who have experienced treatment failure or loss of response on other systemic therapies. What does this study add? In this subgroup analysis of AMAGINE‐2/‐3, patients who had been rescued with brodalumab at week 16 after experiencing inadequate response to ustekinumab had higher skin clearance rates at week 52 (72·6%, 58·1% and 36·3% achieved Psoriasis Area and Severity Index ≥ 75%, ≥ 90% and 100% improvement, respectively) than patients who continued on ustekinumab (61·7%, 25·5% and 5·4%, respectively). Brodalumab may be effective in patients who have inadequate responses to ustekinumab. Linked Comment:  Montaudié. Br J Dermatol 2019;180 :255–256 . Plain language summary available online Respond to this article